1973
DOI: 10.2136/sssaj1973.03615995003700050041x
|View full text |Cite
|
Sign up to set email alerts
|

Forest Windthrows and Their Influence on Soil Morphology

Abstract: The variability in thickness of the O and A2 horizons was studied on a sandy loam forest soil in the Great Lakes‐St. Lawrence Region of southern Ontario. Horizon thicknesses were recorded in 1.3 cm (0.5 inch) classes for each 10.2 cm (4 inches) of horizontal distance on the faces of each soilpit. Soilpits were located both subjectively on windthrows and randomly in the study area. Thickness frequency distributions for O horizons were normal and for the A2 horizons Poisson‐like. Both were independent of recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…During the last 11 years, the ecosystems of the Peninsula of Baja California have been seriously disturbed by the hurricanes Lisa 1976, Guillermo 1979and Paul 1983 Uprooting, contrasts with the other types of death; it generates considerable microenvironment alterations. Uprooted trees not only produce the biggest patches (Table 2), but also change soil development and affect gap regeneration by removing the root substratum, and hence the seed bank (Armson & Fessenden 1973). Therefore, future studies should include continuous surveys of species colonization and establishment within gaps created by uprooted trees.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 11 years, the ecosystems of the Peninsula of Baja California have been seriously disturbed by the hurricanes Lisa 1976, Guillermo 1979and Paul 1983 Uprooting, contrasts with the other types of death; it generates considerable microenvironment alterations. Uprooted trees not only produce the biggest patches (Table 2), but also change soil development and affect gap regeneration by removing the root substratum, and hence the seed bank (Armson & Fessenden 1973). Therefore, future studies should include continuous surveys of species colonization and establishment within gaps created by uprooted trees.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of rejuvenation is affected, in part, by soil wetness and the depth to horizons which restrict rooting mechanically (Muel-ler and Cline 1959). Soil morphological features in disturbed areas are largely independent of recent cover type and fire history (Armson and Fessenden 1973). Arbroturbation has a bearing upon thickness of solum horizons (Armson and Fessenden 1973) and significantly affects most physical properties (Lutz 1940) as well as the chemical properties of podzolic B horizons (Brown 1979).…”
mentioning
confidence: 99%
“…Soil morphological features in disturbed areas are largely independent of recent cover type and fire history (Armson and Fessenden 1973). Arbroturbation has a bearing upon thickness of solum horizons (Armson and Fessenden 1973) and significantly affects most physical properties (Lutz 1940) as well as the chemical properties of podzolic B horizons (Brown 1979). This variability in distribution and character of the microrelief has important land management implications, particularly in silvicultural programs (Lyford and Maclean 1966 (Dumanski 1978).…”
mentioning
confidence: 99%
“…Paleoroot channels are frequently found infilled with younger material from the overlying cover deposits. The effect of tree-fall on soil disturbance is well documented in the literature (Stephens 1956;Lyford & MacLean 1966;Armson & Fessenden 1973;Dudas & Harward 1975;Brewer & Merritt 1978). Although only 1 study of this nature has been reported in New Zealand (Laffan 1979), many instances of large-scale tree-fall have been cited (e.g., Cranwell & Moore 1936;Zotov et al 1938;Conway 1959).…”
Section: Mechanisms For the Physical Mixing Of Thin Tephra Depositsmentioning
confidence: 93%